Space and secularism: Laïcité, spatial governmentality, and exclusion in French hijab stories. (March 2023) - Almeida, Dimitri
The article frames current practices of French laïcité in terms of spatial governmentality. It builds upon this notion to explore spatialised representations of religion and secularism in 'hijab stories' (narratives of the self that focus on the daily experiences of women who wear a hijab). The analysis of Fatimata Diallo's Sous mon voile and Nargesse Bibimoune's Confidence à mon voile reveals an ever-expansive reach of an exclusionary reading of laïcité . This phenomenon has severely restricted the spatial practice of hijabi women in French society favouring adaptive strategies that include the creation of counter-spaces of subjectivation and self-expression.